THE ENERGY PROVISION DILEMMA OF COAL VERSUS WIND FROM THE ECONOMIC, ENVIRONMENTAL, AND SOCIAL PERSPECTIVE WITHIN THE ENERGY SECURITY FRAMEWORK - Asri, Novena Damar; Yusgiantoro, Purnomo (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2020)
The energy security principle demands the fulfillment of availability, acceptability, affordability, accessibility, and sustainability. Under the financial constraints, it is very challenging to achieve. As a result, immediate decisions, often only based on the lowest cost neglecting the overall impacts, are taken. This study aims to reveal the energy provision dilemma through a literature review method and simple calculation analysis. This study intends to exemplify how to conduct an equitable analysis by comparing wind and coal power plants’ impacts from the economic, environmental, and social perspectives. This study finds that the mutually complement characteristics of NRE (New and Renewable Energy) and non-NRE (fossil energy sources) raise a dilemma in selecting the energy source, where the financial constraints exaggerate the dilemma. The study also finds that the electricity generating cost of coal is cheaper than wind, but the external costs turn over the result. Coal damages the environment more than wind, but the impacts are often neglected, and society bears the cost. A simple adsorption method could minimize the impacts, but it depends on the producers’ willingness to conduct, which eventually by the consumers’ willingness to pay the higher price. In the social aspect, both power plants have relatively more equal indirect impacts, but coal’s direct impacts are more detrimental than wind. While an energy source may excel the other, considering the specific circumstances is a must. Financial constraints aggravate the developing countries’ dilemma between achieving energy security or fulfilling the basic needs and pursuing economic growth